Effect of crushed sand on mortar and concrete rheology - O. A. Cabrera; L. P. Traversa; N. F. Ortega (Materiales de Construccion, 2011)
This article describes an experimental study conducted on fresh mortars and concretes made with crushed sand. The aim of this research was to assess the effect of aggregate particle shape and surface texture as well as dust content on mortar and concrete rheology. The experimental programme also addressed the impact of angular grains on chemical admixture performance and concrete bleeding. The findings showed that the use of crushed sand induces rheological behaviour that differs from the behaviour observed in natural sand and that superplasticisers can improve this behaviour considerably.